Quality control of the traditional herbs and herbal products: a review - Amruta Balekundri; Vinodhkumar Mannur (SpringerOpen, 2020)
Abstract Background Herbal medicinal material and product need is increasing, and with this increase in the need, it is very much an essential requirement to maintain the quality of them. Main body The quality of the herbals is altered by various physical, chemical, and geographical aspects which contribute to the quality of these materials. Apart from that, adulteration is also an increasing concern when it comes to herbal material quality. Various chemical and phytochemical test, analytical techniques, and hyphenated analytical techniques are used for determining the quality aspects of the herbal materials in the herbal pharmaceuticals. Conclusion These techniques can be used as quality control tool in assessing the quality of herbal materials and herbal pharmaceuticals.